2017
DOI: 10.1111/apm.12753
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characterization of a nosocomial outbreak of extended spectrum β‐lactamase Escherichia coli ST‐131 confirms the clinical value of core genome multilocus sequence typing

Abstract: Enhanced precision of epidemiological typing in clinically suspected nosocomial outbreaks is crucial. Our aim was to investigate whether single nucleotide polymorphism (SNP) analysis and core genome (cg) multilocus sequence typing (MLST) of whole genome sequencing (WGS) data would more reliably identify a nosocomial outbreak, compared to earlier molecular typing methods. Sixteen isolates from a nosocomial outbreak of ESBL E. coli ST-131 in southeastern Sweden and three control strains were subjected to WGS. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The genomic analyses showed that clonal dissemination of mcr-carrying Enterobacterales in Emilia-Romagna was limited compared to horizontal gene transfer through plasmids or transposable element dissemination. In addition, the minimal pairwise distance observed between isolates belonging to the same genomic cluster (i.e., 138 SNPs) was much higher than usually observed in nosocomial clonal infections [33]. This suggests that E. coli lineages carrying mcr did not clonally spread within the regional hospital system.…”
Section: Discussionmentioning
confidence: 80%
“…The genomic analyses showed that clonal dissemination of mcr-carrying Enterobacterales in Emilia-Romagna was limited compared to horizontal gene transfer through plasmids or transposable element dissemination. In addition, the minimal pairwise distance observed between isolates belonging to the same genomic cluster (i.e., 138 SNPs) was much higher than usually observed in nosocomial clonal infections [33]. This suggests that E. coli lineages carrying mcr did not clonally spread within the regional hospital system.…”
Section: Discussionmentioning
confidence: 80%
“…Unfortunately, due to poor metadata pertaining to such strains, little insight can be gained into the origins of these samples, highlighting the importance of researcher diligence in uploading metadata sufficient to facilitate epidemiological investigations; such situations are commonplace when utilizing online sequence repositories. It does, however, indicate a potential shared origin of these strains which, by metrics used in other research, may constitute clonal outbreaks (Woksepp et al, 2017). This data highlights the value of EnteroBase, and other similar tools such as BacWGSTdb (Ruan and Feng, 2016), in the undertaking of investigations involving en-masse genotypic and phylogenomic characterization; an increasingly important area of research as AMR prospects continue to worsen at a global level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SNV-based methods, IRIDA provides functionality for performing MLST. Current MLST approaches that extend classical MLST schemes to include an organism's core genome (cgMLST) or whole genome (wgMLST) have been validated for surveillance of foodborne disease, and are quickly being adopted by surveillance programs such as PulseNet International, and used for a variety of nosocomial, zoonotic, and tuberculosis outbreaks (45)(46)(47)(48)(49). IRIDA has adopted the fast, accurate, and computationally efficient MentaLiST system as its main pipeline for cgMLST-based analysis.…”
Section: Irida Performs Analyses Of Sequence Data and Metadata With Vmentioning
confidence: 99%